2023
DOI: 10.1037/amp0001044
|View full text |Cite
|
Sign up to set email alerts
|

A person-centered approach to capture health disparities and multidimensional impact of COVID-related stressors.

Abstract: The COVID-19 pandemic has influenced people's lives in diverse ways. The authors utilized latent class analysis (LCA), a person-centered approach, to examine distinct patterns of COVID-related stressors and their associations with alcohol-related, mental health, and quality of life outcomes. Participants were 463 adults who completed the baseline assessment of the National Institute on Alcohol Abuse and Alcoholism COVID-19 Pandemic Impact on Alcohol Study from June 2020 to January 2022. Using cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
3
8
0
Order By: Relevance
“…Consistent with prior studies, 20,22 3 distinct latent classes of negative COVID-19 impacts and their associations with psychological distress were identified. A detailed discussion of the 3 latent classes can be found elsewhere.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with prior studies, 20,22 3 distinct latent classes of negative COVID-19 impacts and their associations with psychological distress were identified. A detailed discussion of the 3 latent classes can be found elsewhere.…”
Section: Discussionsupporting
confidence: 86%
“…21 Likewise, Luk et al explored the multidimensional impact of COVID-related stressors and yielded 4 classes; compared to those in Minimal COVID-related Impact class, people in Serious Financial Stress class reported higher levels of perceived stress, anxiety, and depressive symptoms. 22 These studies suggest that individuals experiencing a more severe level of COVID-19 impacts are at higher risk for psychological distress than those who are less affected by the pandemic. As the pandemic persists, negative COVID-19 impacts may further increase the incidence of mental health conditions, 4 and their long-standing effects can vary across the adult life span.…”
Section: Multidimensional Covid-19 Impacts and Mental Health Outcomesmentioning
confidence: 99%
“…Participants who were unemployed when they completed our survey also were more likely than those who were employed to populate the distressed or the at-risk clusters. Other studies have found that financial instability has been associated with an increased risk of developing mental health problems during the COVID-19 pandemic [ 89 , 90 , 91 ]. Financial security is likely to be less prevalent among young adults who do not have a regular income, which could trigger economic anxiety [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, across these studies, the fact that many parents fell into lowrisk groups despite the enormous upheaval to their daily lives may signal resilience. On the other hand, it is notable that there was a dose-response effect, wherein children, adolescents, and families exposed to more pandemic-related stress are at risk for more adverse outcomes, in line with a cumulative risk model (Luk et al, 2023;McLaughlin et al, 2022). Taken together, though the social and economic burden of the pandemic was disproportionately carried by families with existing hardship, it nonetheless had a ubiquitous effect on the daily lives of families at a global level.…”
Section: Daily Upheavalmentioning
confidence: 98%
“…Moreover, the pandemic has exacerbated social determinants of health and mental health inequalities. The social and economic impact of the pandemic was larger for marginalized families—many of whom had tenuous situations prior to rising rates of unemployment, wage loss, food insecurity, disrupted education, housing instability/houselessness, and discrimination/stigmatization (Gibson et al, 2021; Luk et al, 2023; World Health Organization, 2021). The toll of the pandemic on vulnerable groups was linked to differential stress, adversity, and mental health impact (McLaughlin et al, 2022).…”
Section: What Is Next?mentioning
confidence: 99%